2013
DOI: 10.1021/ja408678p
|View full text |Cite
|
Sign up to set email alerts
|

Dihaloiodoarenes: α,α-Dihalogenation of Phenylacetate Derivatives

Abstract: A hypervalent iodine reagent-based α-carbonyl dihalogenation reaction is reported. Treating diazoacetate derivatives with either iodobenzene dichloride or iodotoluene difluoride results in gem-dichlorination or gem-difluorination products, respectively. The reaction is catalyzed by either Lewis acid or Lewis base activation of the aryl-λ(3)-iodane (ArIX2) species and proceeds rapidly and chemoselectively to the desired gem-difunctionalized products in good to excellent yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 50 publications
1
64
0
Order By: Relevance
“…More recent approaches include the use of iodobenzene dichloride to convert diazoacetates into gem-dichlorinated products, in high yield in dichloromethane, a process activated by pyridine (Scheme 230). 537 Methods for introduction of a single fluorine substituent continue to attract attention. Moody and co-workers have developed an approach based on nucleophilic fluorination rather than the more commonly used electrophilic reagents.…”
Section: S−h Insertionmentioning
confidence: 99%
“…More recent approaches include the use of iodobenzene dichloride to convert diazoacetates into gem-dichlorinated products, in high yield in dichloromethane, a process activated by pyridine (Scheme 230). 537 Methods for introduction of a single fluorine substituent continue to attract attention. Moody and co-workers have developed an approach based on nucleophilic fluorination rather than the more commonly used electrophilic reagents.…”
Section: S−h Insertionmentioning
confidence: 99%
“…The modern resurgence in the use of these as synthetic reagents stems from their broad reactivity profiles and the mild, environmentally benign conditions associated with their transformations. This has been successful, enabling the gem-dichlorination and gem-difluorination of a variety of diazoesters 13 (Scheme 1a and b) and diazooxindoles 14 (Scheme 1c). One often-encountered example is the α-carbonyl functionalization reaction 6 that either transfers one of the iodane ligands (e.g.…”
mentioning
confidence: 99%
“…An impressive recent example demonstrating the divergent opportunities in halogenation reactions when using hypervalent iodine(III) reagents was reported by Murphy and co‐workers . They showed that diazoesters, such as 14 a , readily give the α,α‐dichlorinated products 15 in excellent yields (67–95 %; Scheme ) through a double ligand transfer from PhICl 2 ( 1 ). Addition of catalytic amounts of pyridine (5 mol %) greatly accelerated the reaction rate, furnishing the chloro esters 15 within minutes.…”
Section: Halogenations Using Hypervalent Iodine(iii) Reagentsmentioning
confidence: 99%